Performance of IITA developed cassava postharvest technologies - Jeon, Y.; Halos, L. (1991)
The paper describes the package of postharvest equipment for processing Cassava into various forms of food products. Field performance features are presented in terms of effect on system efficiency and some measurable socio-economic impact. Technology development strategies derived from the fie ld testing are discussed.